Pricing Strategy of the Leading Container Shipping Carriers under the Turbulent Freight Market and its Impact on Logistics Supply Chains; an Analytical Approach - Andrzej S. GRZELAKOWSKI (Communications of International Proceedings, 2023)
Covid-19 pandemic crisis seriously hit both the global trade and logistics sectors, causing huge distortions of the global supply chains. A peculiar paradox of this crisis, however, was an unexpectedly rapid growth in demand for container shipping services and, as a result of this, an unprecedented behavior of global container shipowners in the recovery phase. The main purpose of the research is to identify and analyze the basic premises and factors determining the implementation of an aggressive and typically pro-fiscal pricing strategy by maritime container operators, as well as to assess the economic consequences of such a long-term use of exorbitantly high freight rates. There were applied such research methods and techniques as: desk research and data exploration as well the factors analysis (FA). Moreover, there were conducted interviews with few representatives of the container shipping operators and forwarders. The obtained research findings indicate that the adopted pricing strategy was strongly oriented on maximal exploring such an extraordinary market opportunity by the container carriers, what enabled them gaining huge revenues and profits to the detriment of other companies. This has initiated significant changes in the existing business model of the container shipping operators. There is an inconsistency between the market regulatory mechanism as a main economic driving force of container shipping carriers in the operational sphere and the international public regulatory system. The latter one should be modified to adapt it better to the changes that have taken place on the global container shipping market.
Keywords: container shipping market; freight and charter indices; pricing strategies; supply chains’ disruptions